Organic Creativity and the Physics Within - Edited by Johan F. Hoorn (John Benjamins Publishing Company, 2013)
A group of international top scientists from a diversity of disciplines sat together for five days with artists, designers, and entrepreneurs to develop a trans-disciplinary theory of creativity. Organic Creativity and the Physics Within assumes that creativity is a quality of nature visible in physics as well as in psychology, its basis being combinatorics, coincidence, complementarity, and fractal emergence. The authors prompt a mechanism cutting through particle physics, perception, psychology, and culminating into playfulness. Organic Creativity and the Physics Within connects us to the universality of nature's creativeness.